Гидрометаллургия железных порошков - Буланов В. Я. Владимир Яковлевич; Ватолин Н. А. Николай Анатольевич; Залазинский Г. Г. Георгий Георгиевич; Волкова П. И. Полина Ивановна; Щепеткин А. А. (Москва, Наука, 1984)
Авт. указаны на обл.